Sweden Finns in Stockholm: Mental health, health-related experiences, and needs ... - Strand, Mattias (OSF Registries, 2022)
Sweden Finns are one of five officially recognized national minorities in Sweden, alongside the Sami, Tornedalians, Romani, and Jews. Their national minority status is based on the far-reaching historical roots of Finns and the Finnish language in Sweden, which is to a large extent due to the fact that what is nowadays Finland was a part of the Swedish nation until 1809. Today’s Finnish-speaking population in Sweden has mostly migrated to Sweden in the modern era. In general, three waves of migration from Finland to Sweden can be outlined: i) The approximately 70 000 so-called Finnish war children who were evacuated to Sweden during World War II for humanitarian reasons, of which around 7 100 were subsequently adopted by their foster families and remained in the country. ii) The large population of Finnish migrant workers who primarily came to Sweden during the 1960s and 1970s, when more than 300 000 Finns were recruited to meet the large needs of the Swedish post-war industrial sector. iii) The (on group ...